Comparison of scleral buckling using wide-angle viewing systems and indirect ophthalmoscope for rhegmatogenous retinal detachment - Li, Xiu-Juan (Int J Ophthalmol, 2016)
AIM: To compare the effects of scleral buckling using wide-angle viewing systems (WAVS) with that using indirect ophthalmoscope for the treatment of rhegmatogenous retinal detachment. METHODS: The study was a retrospective analyses of the medical records of 94 eyes (94 patients) with rhegmatogenous retinal detachment. Among them, 47 eyes underwent scleral buckling using WAVS with endoilluminator (Group W), and 47 eyes underwent scleral buckling using indirect ophthalmoscope (Group I). Surgical durations, primary success rate, best-corrected visual acuities (BCVA), delayed subretinal fluid absorptions and surgical complications were compared between the two groups. RESULTS: At baseline, there were no statistical differences between the two groups in patient's age (P=0.997), gender (P=0.853), symptom duration (P=0.216), BCVA (P=0.389), refractive error (P=0.167), intraocular pressure (P=0.595), the number of retinal breaks (P=0.832), the extent of retinal detachment (P=0.246), subretinal demarcation line (P=0.801), and macular detachment (P=0.811). The follow-up period was 12mo. The surgical durations in Group W (with or without encircling buckling) were significant shorter than those in Group I (P<0.001 respectively). The primary success rate was 94.27% in Group W, which was similar to that in Group I (92.38%, P = 0.931). The BCVA in Group W was better than that in Group I (P<0.001) at 1-month follow-up visit. However, there were no significant differences between the two groups at 3-month (P=0.221), 6-month (P=0.674), and 12-month (P=0.363) follow-up visits respectively. Delayed subretinal fluid absorptions were more common in Group I than in Group W at 1-month (P=0.045) follow-up visit, but there were no significant differences between the two groups at 3-month (P=0.111), 6-month (P=1.000) and 12-month follow-up visits respectively. CONCLUSION: Scleral buckling using WAVS can be an alternative choose for rhegmatogenous retinal detachment.